Gestión administrativa en la Compañía de Taxis San Rafael, servicio de taxi convencional Venzapcom S.A. - Rivera Peñas, Nathaly Julissa (2020)
This work was carried out with the purpose of studying how administrative management is developing within the Compañía de Taxis San Rafael, Servicio de Taxis Convencional VENZAPCOM S.A., analyzing the factors that are affecting, significantly since currently administrative management has become a primary axis to lead the company to success and if it is neglected it will lead the organization to failure. Administrative management is based on the correct use of the company's resources, starting with human talent, since an organization with capable members is a productive organization. To obtain the real information of the situation, a survey carried out among the 21 partners of the company was used as a research instrument, based on the descriptive research method, since this method helps you to evaluate some characteristics of a particular situation through of data collection. Through this research it was possible to know specifically what are the factors causing inadequate administrative management within the institution. In the conclusions, these factors could be specifically described, including bad interpersonal relationships among members, non-attendance at work meetings, lack of administrative skills, poor communication, lack of commitment to the company, among others. Therefore, it is vital that consideration be given to paying due attention to these factors that are affecting the administrative management in the organization and taking corrective measures based on adequate planning.